Islamic Family and Child Protection Law’s Perspective On Violence Against Children - Beni Chandra; Toha Andiko (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2020)
The Indonesian Government guarantees the rights and protection of children by Act 35 of 2014 concerning Child Protection. The law provides absolute protection for children against physical and psychological violence that they may receive, but on the other hand there is an interest in Moslem’s families to educate their children according to Islamic law (fiqh), so that there is a contradiction both of them. This research was conducted to determine the view of Islamic family and positive law on the problem of handling and protecting children and the limits of violence against children. The researchers used a comparative approach and library research method. Based on the research conducted, it is found that Islamic family and positive law go in line to provide protection for children. The differences are in the perspective of “children”, violence against children, the application of physical and psychological punishment, and actions against perpetrators of violence. In addition, there are limits to acts of both physical and psychological violence as a preventive and repressive measure against children, according to the provisions of Islamic family law